2007
DOI: 10.5194/acp-7-535-2007
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the aerosol indirect effect under contrasting environments during the ACE-2 experiment

Abstract: Abstract. The Active Tracer High-resolution Atmospheric Model (ATHAM) has been adopted to examine the aerosol indirect effect in contrasting clean and polluted cloudy boundary layers during the Second Aerosol Characterization Experiment (ACE-2). Model results are in good agreement with available in-situ observations, which provides confidence in the results of ATHAM.Sensitivity tests have been conducted to examine the response of the cloud fraction (CF), cloud liquid water path (LWP), and cloud optical depth (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…However, ship track studies show that anthropogenic aerosols can lead to less liquid water (Platnick et al, 2000;Coakley and Walsh, 2002), and satellite studies show both decreases and increases in LWP with increasing aerosols (Kaufman et al, 2005;Matsui et al, 2006). CRM studies have suggested that LWP can either increase or decrease with increasing aerosols, depending on the meteorological conditions (Ackerman et al, 2004;Jiang et al, 2006;Guo et al, 2007;Xue et al, 2008;Small et al, 2009). The decreasing LWP with increasing aerosols can be attributed to enhanced entrainment of dry air or enhanced evaporation of the more numerous smaller cloud droplets in polluted clouds.…”
Section: Comparison With Cam5mentioning
confidence: 99%
“…However, ship track studies show that anthropogenic aerosols can lead to less liquid water (Platnick et al, 2000;Coakley and Walsh, 2002), and satellite studies show both decreases and increases in LWP with increasing aerosols (Kaufman et al, 2005;Matsui et al, 2006). CRM studies have suggested that LWP can either increase or decrease with increasing aerosols, depending on the meteorological conditions (Ackerman et al, 2004;Jiang et al, 2006;Guo et al, 2007;Xue et al, 2008;Small et al, 2009). The decreasing LWP with increasing aerosols can be attributed to enhanced entrainment of dry air or enhanced evaporation of the more numerous smaller cloud droplets in polluted clouds.…”
Section: Comparison With Cam5mentioning
confidence: 99%
“…Note that CF here is defined as the fraction of cloudy columns, and a cloudy column is a column containing one or more cloudy cells with liquid water mixing ratio >0.01 g/kg. The AIE (shortwave plus longwave) at the top-of-the-atmosphere is estimated by swapping the aerosol and meteorological conditions between the "CLEAN" and "POLL" cases and then calculating the radiative flux difference between the clean and polluted aerosol conditions under the same meteorological background (Guo et al, 2007b).…”
Section: Sensitivity To the Relative Dispersion (ε)mentioning
confidence: 99%
“…Consequently, the "CLEAN" clouds transform quickly from one stage (with efficient drizzle production) to another stage (between drizzling and non-drizzling). But for the "POLL" case, due to their continental origin and the strong large-scale subsidence (Guo et al, 2007b), these "POLL" clouds tend to precipitate less efficiently. Moreover, as shown in Fig.…”
Section: Sensitivity To the Relative Dispersion (ε)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results regarding the hypothesized increase in cloud albedo or cloud optical thickness (COT) due to smaller and more numerous droplets, are however not as consistent. Some studies (Sporre et al, 2012;Chameides et al, 2002;Guo et al, 2007) have indeed found that the COT increases in polluted air masses while other studies find no correlation between COT and higher particle concentrations (Twohy et al, 2005;Costantino and Breon, 2013). The reasons for the diverging results are thought to be enhanced entrainment of dry air into the clouds due increased cloud droplet number concentrations (Ackerman et al, 2004;Wood, 2007;Bretherton et al, 2007) or/and that air masses with higher aerosol loading often are associated with drier meteorological conditions (Brenguier et al, 2003).…”
Section: Introductionmentioning
confidence: 99%